2015
DOI: 10.15561/18189172.2015.0811
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Two Tapering Methods on Interleukin-6, Cortisol and Performance in Elite Male Wrestler

Abstract: Abstract.Purpose: This study examined that effect of two types of tapering on interleukin-6(IL-6), cortisol and performance in elite male wrestler. Material: After 4 weeks of progressive training, wrestlers were randomly divided into three equal groups, 1-control group (N=10) continued performing progressive training for one week, 2-taper group 1 (N=10) continued with a 50% reduction in training volume for one week, 3-taper group 2 (N=10) continued with a 75% reduction in volume of training for one week .plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…From positions of pre-nosological diagnostic it can be interpreted as result of loads' feasibility, for overcoming of which organism needs only its own adaptation reserves. Table 2 data reflect stability of adaptation processes of elite sportsmen as well as formation of adaptation trace, which is analogous to the described in work by Meerson and Pshennikova (1988). Changes in less experienced sportsmen shall be understood as tension of LP-AOS system and its passing to new level of functioning.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…From positions of pre-nosological diagnostic it can be interpreted as result of loads' feasibility, for overcoming of which organism needs only its own adaptation reserves. Table 2 data reflect stability of adaptation processes of elite sportsmen as well as formation of adaptation trace, which is analogous to the described in work by Meerson and Pshennikova (1988). Changes in less experienced sportsmen shall be understood as tension of LP-AOS system and its passing to new level of functioning.…”
Section: Discussionmentioning
confidence: 69%
“…creation of excessive free radicals (Blinova, Troshin, et al, 2013;Asghar, Ameghani, et al, 2014;Mehranpour, Silalerdetkul, et al, 2015). With insufficient system of antioxidant protection (AOS) their impact on membranes can result in disorders of sportsman's organism, decrease of his workability and efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…However, a higher reduction in the training volume, longer duration of the taper or both may be required to allow the fatigue to dissipate after an overload period (22,24). Mehranpour et al (16) demonstrated that a 75% reduction in the training load resulted in more favorable changes in the neuromuscular performance and serum hormone concentrations than a 50% reduction in male wrestlers over a 1-week tapering period. Taking together, these results suggest that a higher volume reduction rate at the beginning of the taper may be more beneficial if the preceding training period has been designed to induce some overreaching.…”
Section: Discussionmentioning
confidence: 99%
“…Substantiation of test selection for evaluation of wrestlers' level of fitness (Lozhechka, 2012;Latyshev, 2013), account for athlete individual features (Latyshev, & Korobeynikov, 2013;Kozina, Jagiello, & Jagiello, 2015;Korobeynikov, Latyshev, Latyshev, Goraschenko, & Korobeynikova, 2016), monitoring of athlete's heart rate status (Liu, 2015), the level of basic technical preparation (Iermakov, & Boychenko, 2010;Jagiello, Dornowski, & Wolska, 2014), search for optimum variants to improve work capacity and action performance (Chistyakova, 2012;Mehranpou, Silalerdetkul, Hasani, & Witid, 2015;Tropin, & Pashkov, 2015), account for biomechanical regularities of motor action organization ( Adashevskiy Iermakov, & Gritsyuk, 2010;Adashevskiy, Dylewski, & Iermakov, 2011;Muntian, 2013;Vladimir, & Marian, 2015;Wilke, Fleckenstein, Krause, Vogt, & Banzer, 2016) are of tremendous importance in combat sports. In these cases it is recommended…”
Section: Introductionmentioning
confidence: 99%